KEWENANGAN BADAN PENYELESAIAN SENGKETA KONSUMEN DALAM MENANGANI SENGKETA ASURANSI (CONTOH KASUS DALAM PUTUSAN NOMOR 320/PDT.G/2019/PN MDN) - Arthuro Richie Gunawan; Amad Sudiro (Fakultas Hukum Universitas Tarumanagara, 2022)
Disputes can occur in various sectors and one of them is the insurance sector. Disputes that arise between 2 or more parties can be resolved either through courts or through alternative dispute resolution institutions (known as “LAPS”), which based on legal regulations in effect until 2019 the Indonesian Insurance Mediation and Arbitration Institution (known as “BMAI”) is an alternative dispute resolution institution established for the insurance sector. One example of a dispute in the insurance sector that was settled through alternative dispute resolution procedure is the case of District Court Decision Number 320/Pdt.G/2019/ PN Mdn, which in that case the Consumer Dispute Settlement Institution (known as “BPSK”) of Medan City settled the dispute, even though the insurance company had stated that it was not willing to settle the dispute through Consumer Dispute Settlement Institution of Medan City, because it had been agreed beforehand that if a dispute ever arise between the insurance company and parties related with the Insurance Policy the dispute would be resolved either through the Indonesian Insurance Mediation and Arbitration Institution or District Court. Even so, the Consumer Dispute Settlement Institution of Medan City continued to issue a decision on the dispute, which means that there is a legal problem, where the law in practice is not in accordance with the law in reality. Based on the applicable laws and regulations that are in effect at that time, the Consumer Dispute Settlement Institution of Medan City was not authorised to settle that insurance dispute.